Diagnostic accuracy of ultrasonography for detecting nasogastric tube (NGT) placement in adults: A systematic review and meta analysis. (June 2017) - Lin, Tian; Gifford, Wendy; Lan, Yutao; Qin, Xiuqun; Liu, Xuelian; Wang, Juan; Yang, Biping; You, Tianhui; Chen, Ken
Abstract: Objective: To review the evidence on diagnostic accuracy of ultrasonography for detecting correct nasogastric tube (NGT) placement in adults compared to X-ray as the reference standard. Methods: This is a systematic review and meta-analysis of observational studies, searched in the literature between 1961 and 2015. We included studies which compared the diagnostic accuracy of ultrasonography detection for NGT placement with X-ray in adult patients who were undergoing NGT placement for any reason in any care setting. We searched published studies in the following electronic databases: Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, CINAHL, Web of Science, WanFang Data, China Journal Net, and the Chinese Biomedical Literature Database. Both English and non-English-language articles were retrieved. Risk of bias was assessed using a standard procedure according to the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) criteria. Results: We included five studies involving a total of 420 adult patients undergoing nasogastric tube placement: three trials were undertaken in mechanically ventilated patients in prehospital settings and two involved participants with comma or severe trauma in emergency room or intensive care unit (ICU). Pooled results showed that ultrasonography had a sensitivity of 0.93 (95% CI 0.87 to 0.97), and specificity of 0.97 (95% CI 0. 23 to 1.00), suggesting that diagnostic performance of ultrasound is useful to confirm correct NGT placement, but not optimal to detect incorrect NGT position. This was confirmed through a summary receiver operator characteristics (SROC) curve that showed the area under the curve was 0.96 (95% CI 0.94 to 0.98). Discussion: The main limitation of the review is the relatively moderate level of heterogeneity of included studies which may partially undermine the reliability and reproducibility of results. The insufficient studies included did not allow identification of possible sources of heterogeneity and exploration of reporting bias. Due to heterogeneity of studies, the diagnostic performance of ultrasonography could only be drawn cautiously. Physicians and nurses should perform routine X-ray if visualization of NGT is not possible. More well designed studies exploring ultrasound as a diagnostic tool for accuracy of NGT placement are needed to strengthen the current evidence.